Tools, Strategies, and Practices for Modern and Accountable Public Sector Management - Azevedo, G.; Oliveira, J.; Rui Marques; Augusta Ferreira (2019)
The recent global financial and economic crisis has had surprising effects on several economies worldwide. This global event has promoted the discussion on how ethical, transparent, and rigorous the accountability of public sector institutions is. However, public manager accountability is translated into a vision that goes beyond its sphere of activity, demanding information on how public resources have been managed based on the maximization of social welfare and sustainable development. Tools, Strategies, and Practices for Modern and Accountable Public Sector Management is an essential reference source that discusses the process behind how public resources are managed as well as how they are coordinated to achieve collective success. Featuring research on topics such as corporate responsibility, fiscal accountability, and public administration, this book is ideally designed for researchers, managers, financial authorities, auditors, public managers, public administrators, regulatory authorities, accountants, professionals, and students involved with the accountability and reform of public management in local governments.